Ga/HZSM-5 Catalysed Acetic Acid Ketonisation for Upgrading of Biomass Pyrolysis Vapours - Hessam Jahangiri (Catalysts, 2019)
Pyrolysis bio-oils contain significant amounts of carboxylic acids which limit their utility as biofuels. Ketonisation of carboxylic acids within biomass pyrolysis vapours is a potential route to upgrade the energy content and stability of the resulting bio-oil condensate, but requires active, selective and coke-resistant solid acid catalysts. Here we explore the vapour phase ketonisation of acetic acid over Ga-doped HZSM-5. Weak Lewis acid sites were identified as the active species responsible for acetic acid ketonisation to acetone at 350 °C and 400 °C. Turnover frequencies were proportional to Ga loading, reaching ~6 min−1 at 400 °C for 10Ga/HZSM-5. Selectivity to the desired acetone product correlated with the weak:strong acid site ratio, being favoured over weak Lewis acid sites and reaching 30% for 10Ga/HZSM-5. Strong Brønsted acidity promoted competing unselective reactions and carbon laydown. 10Ga/HZSM-5 exhibited good stability for over 5 h on-stream acetic acid ketonisation.